Development of the Benefits of Using Manual SOP Therapy in Cases Low Back Pain at Causa Piriformis Syndrome - Marcelia, Riza; Santoso, Totok Budi (GoAcademica Research & Publishing, 2024)
Low Back Pain at Causa Piriformis Syndrome is a musculoskeletal disorder that causes pain in the fifth lumbar and first sacral areas that radiates to the feet and legs due to an abnormal neuromuscular condition of the piriformis muscle or compression or irritation of the sciatic nerve running below through the muscles. muscle. Low back pain itself is something that is common in patients so patients seek medical help, whereas piriformis syndrome is a case that is difficult to diagnose. Electrodiagnostic consultants are often asked to differentiate between piriformis syndrome and radiculopathy. Low back pain at causa piriformis syndrome is caused by activities carried out in the wrong way and carried out repeatedly as well as a lack of education which results in pain in the back and radiating to the legs. This case study aims to find the benefits of physiotherapy intervention in the form of manual therapy such as stretching of the postural muscles, myofascial release, dynamic muscle adaptation, contract relax of the piriformis muscle, hip traction, and physiological movements in the lumbar region and the piriformis muscle. The research method used is a case study. The respondent used was a 48 year old patient who was a housewife who had retired from office work. This research was conducted 8 times for one month. Patients were evaluated using a visual analog scale (VAS). The results of using intervention in the form of manual therapy show a reduction in pain in low back pain at causa piriformis syndrome from a pressure pain scale of 8 to 3, movement pain from 8 to 2 and silent pain from 2 to 1. In conclusion, providing manual therapy intervention has benefits in Reduces pain in the lower back and piriformis syndrome muscle.